Jamaica. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamerica de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Jamaica during 2014 are identified, with respect to the needs and interests of the country, strengthening issues such as financing, family farming, plant quarantine, social management, territorial management, post-harvest management, fishing, inclusion of women and sweet potato and milk production.